Façade 4.0. The new digital life-cycle of the building envelope.'The digital transformation will change everything' – with this quote in mind a deep look into the current façade business will be given with a special attention to digitalization. - Mena Lozada, Tomas; Arztmann, Daniel; Ramírez, Jhosangela (Technische Hochschule Ostwestfalen-Lippe, IDS Institut für Designstrategien, 2021)
This paper provides insights into the current situation from the perspective of an international façade system supplier and gives examples from daily work and scientific research projects. Digitalization influences the façade business already in nearly each planning step. Renderings and visual simulation helps the architect to make decisions in the early planning stage. In addition, the development of 3D visualization has led to the creation of 3D tutorials for installations purposes. Finite element analysis, parametric planning tools and rapid prototyping are used in the façade system development to control design parameters without the necessity of a physical mockup. In the future, the cyber physical systems and 3D-tutorials in combination with synchronization of the data from the digital building twin will lead to zero tolerance fabrication and installation of complex façade products with sensor/motor-interfaces. These sensor driven, automated and interconnected products - like the so-called active noise cancelling façade components - are the base for an intelligent, self-controlled building envelope. Further innovations are expected in the process steps of façade maintenance and upgrading that will have huge consequences regarding a planned and controlled end of life.
Keywords: Fassadenkonstruktion; Glasfassade; Fenster; Digitalisierung; Entwurf; Baumaterial; Bauprodukt; Innovation; Funktionsfähigkeit; 3D-Modell; Visualisierung; Lebenszyklus; Parametrisches Entwerfen; Building Information Modeling; Active Noise Cancelling